PREVALENCE ON THE USE OF ELECTRONIC GADGETS ON CHILDREN HEALTH ON PRIMARY SCHOOLS IN BENGKALIS - Salwa; Usman (Journal of English Language Teaching, Literatures, Applied Linguistic (JELTLAL), 2024)
The use of technological gadgets has rapidly been increasing among adolescents, which may result in health issues and technology addiction. This study focuses on the prevalence of usage of technological gadgets and health-related complications among primary school-going children in Bengkalis. A total of 50 primary school students from 2 different districts of Bengkalis participated in the study. The children were asked questions relating to their access to electronic gadgets, time spent on outdoor activities, and whether they experienced any health-complications as an after-effect of the usage. A binary logistic regression model was adapted considering time spent on gadgets as an independent variable and health problems (physical and mental) as the dependent variable. Based on 57.00% of the participants were reported to use mobile phones on a daily basis. The participants were reported to use gadgets significantly more (P < .05) in 2020 as compared to 2019. Children showed less tendency to spend time in outdoor activities.